The Richness of Inner Experience: Relating Styles of Daydreaming to Creative Processes - Zedelius, Claire M.; Schooler, Jonathan W. (Frontiers in Psychology, 2016)
Psychologists have long hypothesized that daydreaming (i.e. engaging in stimulus-independent, task-unrelated thoughts and images) may facilitate creativity, but evidence for this hypothesis has been mixed. We propose that, to fully understand the relationship between daydreaming and creativity, it is essential to distinguish between different creative processes as well as between alternative styles of daydreaming. A prominent distinction in creativity research is that between analytic problem solving, which involves incremental and largely conscious processes, and insight, which is characterized by the spontaneity with which an idea springs to mind. In this aspect, insight resembles daydreaming. Indeed, recent evidence has linked daydreaming to creative performance. But like creativity, daydreaming is a multifaceted concept. Daydreams vary in style and content, a fact that is receiving little attention in contemporary research. Not all kinds of daydreaming are likely to have the same effects on creativity. We discuss different factors prevalent in people’s daydreaming, such as mood, attentional focus, and intentionality, and consider how these factors may be related to creative processes. We further discuss implications for ways to enhance creativity through deliberate daydreaming practice.